Shifts in growth light optima among diatom species support their succession during the spring bloom in the Arctic - Croteau, D.; Lacour, Thomas; Schiffrine, N.; Morin, P.i.; Forget, M.‐h.; Bruyant, F.; Ferland, J.; Lafond, A.; Campbell, D. A.; Tremblay, J.‐e.; Babin, M.; Lavaud, Johann (Journal of Ecology, 2022)
1. Diatoms of the Arctic Ocean annually experience extreme changes of light environment linked to photoperiodic cycles and seasonal variations of the snow and sea-ice cover extent and thickness which attenuate light penetration in the water column. Arctic diatom communities exploit this complex seasonal dynamic through a well-documented species succession during spring, beginning in sea-ice and culminating in massive phytoplankton blooms underneath sea-ice and in the marginal ice zone. The pattern of diatom taxa sequentially dominating this succession is relatively well conserved interannually, and taxonomic shifts seem to align with habitat transitions. 2. To understand whether differential photoadaptation strategies among diatom taxa explain these recurring succession sequences, we coupled lab experiments with field work in Baffin Bay at 67.5°N. Based on field data, we selected five diatom species typical of different ecological niches and measured their growth rates under light intensity ranges representative of their natural habitats. To characterize their photoacclimative responses, we sampled pigments and total particulate carbon, and conducted 14C-uptake photosynthesis response curves and variable fluorescence measurements. 3. We documented a gradient in species respective light intensity for maximal growth suggesting divergent light response plasticity, which for the most part align with species sequential dominance. Other photophysiological parameters supported this ecophysiological framing, although contrasts were always clear only between succession endmembers, Nitzschia frigida and Chaetoceros neogracilis. To validate that these photoacclimative responses are representative of in situ dynamics, we compared them to the chlorophyll a-specific light-limited slope (α*) and saturated rate of photosynthesis (P*M), monitored in Baffin Bay on sea-ice and planktonic communities. This complementary approach confirmed that unusual responses in α* and P*M as a function of light history intensity are similar ...